2022
DOI: 10.3390/pharmaceutics14102228
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Dissolution of Praziquantel in Biorelevant Media and the Impact of Digestion of Milk on Drug Dissolution

Abstract: Praziquantel is a poorly water-soluble drug used to treat parasitic infections. Previous studies have suggested that its rate and extent of dissolution in milk and biorelevant media are slow and limited compared to dissolution in the pharmacopoeial-recommended medium, despite being reported as displaying a positive food effect upon administration. This study aimed to revisit the dissolution of praziquantel in biorelevant media and milk to better understand this apparent dichotomy. The context of digestion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Notably, the solubility of PZQ is known to be independent from pH variation which might be caused by the presence of MA and TA. 27 To use the in vitro dissolution as a prediction of the in vivo performance of each sample, sink conditions were not maintained during dissolution in order to build up supersaturation, which commonly occurs under finite-volume conditions in the gastro-intestinal tract, and to allow possible events such as nucleation, crystallization, and precipitation to proceed. Hence, at time zero, a suitable amount of the sample to give 60 mg of PZQ was added to the dissolution medium.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the solubility of PZQ is known to be independent from pH variation which might be caused by the presence of MA and TA. 27 To use the in vitro dissolution as a prediction of the in vivo performance of each sample, sink conditions were not maintained during dissolution in order to build up supersaturation, which commonly occurs under finite-volume conditions in the gastro-intestinal tract, and to allow possible events such as nucleation, crystallization, and precipitation to proceed. Hence, at time zero, a suitable amount of the sample to give 60 mg of PZQ was added to the dissolution medium.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been suggested that the lack of attention to the use of milk as a drug delivery vehicle may be a function of the lack of attention given to the importance of post-ingestion milk digestion on the solubility and dissolution of highly lipophilic drugs (32). Along those lines, to identify effective ways to administer this antiparasitic drug to infants in tropical countries, Eason et al examined the dissolution of the poorly soluble drug, praziquantel (BCS class 2 drug) in milk or infant formula and the consequence of adding pancreatic lipase to these dissolution on drug dissolution (33). These results were compared to the solubility and in vitro dissolution of praziquantel in SGF and in simulated intestinal fed and fasted fluids (FeSSIF and FaSSIF, respectively).…”
Section: Using Milk As a Dissolution Mediummentioning
confidence: 99%
“…Previous review articles can be attributed to the different approaches of detection of API. [4][5][6][7][8][9][10][11] Various methods have been developed to determine the PZQ content in different matrices, including high performance liquid chromatography (HPLC), 12,13 liquid chromatography with tandem mass spectrometry (LC-MS/MS), 14,15 near infrared spectroscopy (NIS), 16 and capillary electrophoresis (CE). 17 Electrochemical methods are also attractive since they have simpler less expensive instrumentation that can be portable.…”
Section: Introductionmentioning
confidence: 99%